Effect of 130 keV pulsed electron irradiation on the efficiency of radiative transitions in Eu-doped glass-ceramics CaSiO3 - Gonzales-Lorenzo C.D. (2021)
This work was carried out with partial financial support from Fundaçăo de Amparo à Pesquisa do Estado de Săo Paulo - FAPESP, Brazil (Process number 2014/03085–0 ). To Conselho Nacional de Desenvolvimento Científico e Tecnológico - CNPq, Brazil , for fellowship to C.D. Gonzales-Lorenzo (Process number 162741/2015–4 ). The authors would like to express our thanks to Dr. H. Loro from the National Engineering University (UNI), Peru, for allowing us to use the appropriate equipment for optical absorption measurements. Besides, C.D. Gonzales-Lorenzo kindly acknowledges the partial financial support from Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica (CONCYTEC) - Banco Mundial , through its executing unit FONDECYT , Peru (Process number 037-2019-FONDECYT-BM-INC.INV.). A.F. Zatsepin and A.N. Kiryakov were supported by the Russian Science Foundation (Grant N° 21-12-00392 ) and also the Russian Foundation for Basic Research-RFBR grants N° 20-42-660012 .